2014
DOI: 10.1111/cei.12418
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cell microRNA expression changes in children with acute Kawasaki disease

Abstract: glucocorticoid-induced tumour necrosis factor-receptor (GITR), cytotoxic T lymphocyte antigen (CTLA)-4)] were significantly lower in KD patients (P < 0·05). MiR-155 and miR-21 levelswere significantly down-regulated and miR-31 expression was higher in KD patients (P < 0·05). Plasma interleukin (IL)-6 concentrations, pSTAT-3 protein levels and suppressors of cytokine signalling (SOCS)-1 mRNA expression were remarkably elevated in acute KD (P < 0·05), while pSTAT-5 protein levels were remarkably decreased in acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…These investigators then proposed that this imbalance of Th17/ Treg cells might be involved in disturbing the immune homeostasis in KD. This relationship was also shown by Ni et al [48]. Kuo et al [49] performed a meta-analysis of the ITPKC studies carried out in Taiwanese population and reported a significant association between ITPKC allele rs28493229 and KD (Odd's ratio of 1.36 and 95% confidence interval: 1.12-1.66), especially with the risk of aneurysm formation (p=0.001).…”
Section: Etiopathogenesissupporting
confidence: 60%
“…These investigators then proposed that this imbalance of Th17/ Treg cells might be involved in disturbing the immune homeostasis in KD. This relationship was also shown by Ni et al [48]. Kuo et al [49] performed a meta-analysis of the ITPKC studies carried out in Taiwanese population and reported a significant association between ITPKC allele rs28493229 and KD (Odd's ratio of 1.36 and 95% confidence interval: 1.12-1.66), especially with the risk of aneurysm formation (p=0.001).…”
Section: Etiopathogenesissupporting
confidence: 60%
“…In patients with acute KD, Tregs were shown to decrease not only in numbers, but in function with a downregulation in Treg key regulatory molecules including FOXP3, GITR, and CTLA-4 [55,56]. Downregulation of these key regulatory molecules in acute phase KD is suggested to be the result of increased expression of miR-31, which directly targets FOXP3 mRNA, and decreased expression of miR-155, which is involved in a signaling pathway promoting FOXP3 expression (Table 3) [55]. In another study, whole blood miRNA expression differences were explored between acute KD and adenovirus infection to show significantly higher expression of miR-145 in KD [57].…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…IVIG treatment also reduced the proportion of Th17 cells, as well as the expression of IL‐17. IVIG has been shown to increase T reg proportions and expression of FOXP3 in the acute phase of KD . Furthermore, IVIG treatment in combination with IFX was found to increase the number of T reg cells in patients with KD .…”
Section: Discussionmentioning
confidence: 94%
“…T‐helper type 17 and T reg cells have recently been reported to have an important role in the induction of systemic vasculitis during the acute phase of KD . Th17 cells can produce IL‐17 and lead to tissue damage and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%